Relation between climatic factors, yield, and quality of Pennisetum purpureum cv. Cuba CT-169 in the Cauto Valley, Cuba - Ram?rez, J. L.; Herrera, Rafael Segundo; Leonard, I.; Cisneros, M.; Verdecia, D.; ?lvarez, Y. (Cuban Journal of Agricultural Science, 2011)
Quality and yield data of Pennisetum purpureum cv. Cuba CT-169 were used. The data were from an experiment using a random block design with four replicates, connecting them with climate factors. The experiment was carried out on soil of the fluvisol type, and without fertilization and irrigation. An analysis of linear correlation was performed between the indicators of yield, quality, and climate elements in each period. Besides, multiple linear equations were determined between them. High correlations were obtained (coefficients higher than 0.80) with the rainfall and the average temperature (except for the yield, the percentage of leaves and stems, CP, hemicellulose, ash, and OM). With the relative humidity, ADF, lignin, phosphorus, cellulose, ash, and OM were oustanding in the rainy season. In the rainy season, the yield, CP, CF, cell wall, phosphorus, cell content, hemicellulose, ME and NFE were outstanding. Multiple linear equations were determined and the values of the coefficient of determination were above 0.92. In the rainy season, the highest R2 were obtained for CP, and, in the dry season, for DMD, ME and NFE (P < 0.001). It was established the degree of relation between some climatic factors, the yield, and the quality of the CT-169 in the Cauto Valley. Equation sof multiple linear regression were established relating the yield, CP, CF, lignin, DMD, OMD, ME, and NFE with the rainfall, maximum temperature and humidity. This allows to make an approximate calculation of the indicators, out of the knowledge of the climatic factors. This type of study should be continued with other species and environmental conditions, in a way that the results could be further spread. Key words: pastures, chemical composition, temperature, rainfall, humidity.